THE IMPACT OF CULTURAL TOURISM ON SUSTAINABLE DEVELOPMENT IN UZBEKISTAN. HOW DOES CULTURAL TOURISM CONTRIBUTE TO UZBEKISTAN'S ECONOMY - Tog'ayeva Nargiza, Ibrohimov Zikrillo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article titled "The Impact of Cultural Tourism on Sustainable Development in Uzbekistan" examines how cultural tourism is influencing both the economic and sustainable development of Uzbekistan. It focuses on the integration of tourism with the preservation of the country's rich cultural heritage, which includes its ancient cities, historical landmarks, and vibrant traditions. The article explores the economic contributions of cultural tourism, such as job creation, revenue generation, and stimulation of local businesses, including hospitality, handicrafts, and transportation sectors. Additionally, it delves into the role of cultural tourism in fostering sustainable development by promoting environmental conservation, cultural preservation, and the empowerment of local communities. It emphasizes the need for responsible tourism practices that support both economic growth and the safeguarding of Uzbekistan's unique cultural identity. The article highlights how the government and stakeholders are addressing the challenges of balancing development with sustainability, and the importance of strategic planning in ensuring the long-term success of cultural tourism as a key driver of Uzbekistan’s economy. This theme underscores the potential of cultural tourism as a powerful tool for economic growth while contributing to the overall sustainable development goals of Uzbekistan. The article serves as a valuable resource for understanding the multifaceted impact of cultural tourism on both the national economy and the preservation of cultural heritage.